ANALISIS KEGUNAAN DAN PROSESI ADAT MARSIDUDU (ADAT MANDAILING) BESERTA PEMANFAATANNYA AKAN REMPAH-REMPAH DAN TUMBUHAN UNTUK PEMULIHAN PASCA-PERSALINAN - Nyak Firzah (Jurnal Kesehatan, 2023)
The marsidudu custom comes from Mandailing people for mothers after childbirth (postpartum). This custom can accelerate the discharge of postpartum blood, to warm, and restore the stamina of the mothers. One of the process is dry the vaginal area with the smoke of burned spices or plants. Also, there are who practice marsidudu with steam-bathing process. This research aimed to understand the use, procession, preservation of marsidudu, and the utilization of plants used in marsidudu. This study uses the method of literature review that the characteristic is uses secondary data by reviewing national journals through internet such as Google Scholar and Researchgate with predetermined inclusion criteria. The results have shown that it's practical because it uses the plants that is easy to get, it’s also believed by the Mandailing can improve health, such as reduce pain, clean the reproductive organs, improve blood circulation, and skin rejuvenation of the mothers after childbirth. Thus, traditional culture preserved by this tribe through the generations are also relevant, useful, and have an impact on health aspects to this day.